2023
DOI: 10.3390/inorganics11060260
|View full text |Cite
|
Sign up to set email alerts
|

The Fast Formation of a Highly Active Homogeneous Catalytic System upon the Soft Leaching of Pd Species from a Heterogeneous Pd/C Precursor

Abstract: Understanding the interface between soluble metal complexes and supported metal particles is important in order to reveal reaction mechanisms in a new generation of highly active homogeneous transition metal catalysts. In this study, we show that, in the case of palladium forming on a carbon (Pd/C) catalyst from a soluble Pd(0) complex Pd2dba3, the nature of deposited particles on a carbon surface turns out to be much richer than previously assumed, even if a very simple experimental procedure is utilized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Recently, our research group conducted a study of a specific site of the catalyst at the level of nanoparticles and individual atoms before and after the reaction in cross-coupling. 18,56 The results made it possible to reveal the previously unknown key role of single palladium atoms in C−C cross-coupling reactions; in addition, the study surprisingly suggested that metal nanoparticles can act as catalyst poisons rather than active centers.…”
Section: Dynamic Behavior In Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our research group conducted a study of a specific site of the catalyst at the level of nanoparticles and individual atoms before and after the reaction in cross-coupling. 18,56 The results made it possible to reveal the previously unknown key role of single palladium atoms in C−C cross-coupling reactions; in addition, the study surprisingly suggested that metal nanoparticles can act as catalyst poisons rather than active centers.…”
Section: Dynamic Behavior In Catalysismentioning
confidence: 99%
“…Typically used approaches to study random areas of a catalyst before and after a reaction may lead to “random” results, leaving inaccessible the most useful information for researchers about the behavior of particular catalytic centers in the reaction. Recently, our research group conducted a study of a specific site of the catalyst at the level of nanoparticles and individual atoms before and after the reaction in cross-coupling. , The results made it possible to reveal the previously unknown key role of single palladium atoms in C–C cross-coupling reactions; in addition, the study surprisingly suggested that metal nanoparticles can act as catalyst poisons rather than active centers.…”
Section: Analysis Of the Dynamic Behavior And Variability Of Catalyti...mentioning
confidence: 99%
“…115,116 Reliably distinguishing the nature of the active centers and the type of catalyst (homogeneous or cluster/nanoparticle) is of great significance for tuning the reaction conditions and designing new generations of highly efficient, stable, and sustainable catalysts. 117 Among the various methods, the mercury test (''Hg test'', ''mercury poisoning test'', ''Hg poisoning test'', or ''Hg drop test'') is one of the most frequently used rapid methods for distinguishing between truly homogeneous molecular catalysis and cluster/nanoparticle catalysis. 118 The method is based on the assumption that metallic mercury will poison M0 clusters/ nanoparticles that are acting as catalytically active centers but is inert toward molecular metal complexes.…”
Section: Optimization Of the Reaction Conditions For The C-h Bond Fun...mentioning
confidence: 99%